Cluster Analysis of Determining the Location of Oil Palm Replanting in Mukomuko District - Emlan Fauzi; Linda Harta; Rahmat Oktavia; Sudarmansyah Sudarmansyah; Herlena Bidi Astuti; Jhon Firison; Andi Ishak; Shannora Yuliasari; Yudi Sastro (AGRITROPICA : Journal of Agricultural Sciences, 2020)
Based on oil palm yield data in Bengkulu Province, it shows several regions with varying production numbers. For this reason, it is necessary to group the potential oil palm producing areas to find out which areas produce palm oil in large or small quantities. Production shared is usually done based on the name of the oil palm producing district. Therefore, a method is needed to facilitate the grouping of oil palm producing areas. With the clustering approach, the division of regional groups can be carried out based on planted area and production. Analysis K-Means makes it easier to group an area with the largest, medium and low yields of oil palm. From the analysis results, it can be seen that the priority areas for oil palm rejuvenation in Bengkulu Province are Mukomuko District with locations in Air Rami, Pondok Suguh, Teramang Jaya and Penarik Districts.